Pet stories - Campling, Hannah; Edwards, Daisy; George, Hannah; Longhi, Katya; Moss, Stephanie; Mowat, Claire (Sywell, England igloobooks, 2020)
enjoy a 5 minute story evey night of the week with purr-fect collection meet a surfing tortiose a super-fast hamster a shy puppy and much more! withe 7 fun stories packed with playful pets you'll love sharing these again and again
English stories
For children from 3 to 6 years old
1
Keywords: English stories